KUALITAS LABA SEBELUM DAN SESUDAH ADOPSI IFRS DAN PENGARUHNYA PADA PEMBAYARAN PAJAK PADA PERUSAHAAN CONSUMER GOODS INDUSTRY TAHUN 2008-2012 - Ernie Riswandari (Jurnal Akuntansi Bisnis, 2017)
This research is descriptive research that tests associative quality of earnings before and after the adoption of the IFRS and their effect on the payment of taxes on consumer goods company industry in 2008-2013 are already applying IFRS. A proxy is used for the variable quality of earnings is a non variable using discetionary accruals whereas variables are bound using the corporate income tax provided in the financial statements.Based on paired samples t test test earned the result that there was no difference in the quality of earnings before and after the adoption or implementation of IFRS. Based on regression test in order to answer the second problem formulation that is about how to influence the quality of earnings against the payment of taxes by using available data obtained the result that there was no influence of magnitude of return on kulaitas tax paid before and after adoption of IFRS.Key Words : Quality of Earning, Discretionary Accruals, Tax